Simulação computacional do fluxo hídrico subterrâneo na região do cariri e calibração utilizando gradiente das cargas hidráulicas - Souza, Cláudio Damasceno de (2007)
The main objective of this research is to use a computer code to simulate groundwater flow in an area in the south of the state of Ceará situated between the cities of Crato, Juazeiro do Norte and Barbalha, in the “Cariri” Valley. The computer code used was MODFLOW, a 3-D finite difference groundwater flow model. Two different scenarios we simulated: the rainy and the dry season. Besides, a code using the computer language FORTRAN was developed which proposes an alternate to calibrate the model using hydraulic gradients instead of the usual hydraulic heads as the “objective” functions. This new way of calibrate did not show satisfactory results for the specific area but once it was applied to simple examples it showed promising results.